INTERPRETASI HERMENEUTIKA JORGE J.E. GRACIA DALAM AL-QUR'AN SURAH AL-MAIDAH: 51 - Habibi, M. Dani (QOF, 2019)
This article discusses the interpretation of the Qur’an al-Maidah: 51 using hermeneutic approach Jorge J.E. Gracia. In the 2017 QS. al-Maidah 51 had become the public spotlight because Tjahaja Basuki Purnama or Ahok offensive called QS. al-Maidah: 51 in a speech in the Pulau Seribu. The incident was directly addressed by several Islamic organizations. So it became a problem in the interpretation of the Qur’an that have an impact on the demo in Jakarta. From this background, the researchers want to try to reinterpret QS. al-Maidah: 51 with a hermeneutic approach Jorge J.E. Gracia. Gracia has three functions in the interpretation namely, the function of the history, the meaning and the implications of function. Without discrediting the fruit functions, theory Gracia was very balanced in the interpretation of the text of the Qur’an. Thus, thus, in the interpretive process is expected to be a study of texts of the Qur’an to make Muslims more grown more in addressing the problems of interpretation, especially in the QS. al-Maidah: 51.